Thicker Carotid Intima Media Thickness in Children with Monocyte Chemoattractant Protein-1: A-2138T and A-2464G Mutation - Yuyun Yueniwati; Valentina Yurina; Mohammad Rasjad Indra (Neurology Research International)
Carotid intima media thickness (CIMT) is clearly associated with atherosclerosis. Studies in ischemic stroke patients reveal that there is a significant association between CIMT with monocyte chemoattractant protein-1 (MCP-1) and osteopontin (OPN) promoter polymorphism. This research aims to explain the effect of MCP-1 and OPN promoter polymorphism toward CIMT changes identified in Javanese Indonesian children. Subjects were 54 children: 27 were from parents with ischemic stroke (cases), and 27 were from healthy parents (controlled). The CIMT was examined by utilizing high resolution B-mode ultrasound. Physical examination and genotyping analysis of MCP-1 promoter were conducted by employing PCR method. Research results indicate that two polymorphisms were obtained, that is, A-2138T and G-2464A, respectively. A-2138T polymorphism was found in 5% of case children and in 14.3% of controlled children. G-2464A polymorphism was found in 5% of case children. CIMT of case children was significantly different from that of controlled children (0.61±0.012 mm versus, 0.52±0.015 mm, P= 0.021). Subjects with MCP-1 promoter polymorphism have 1.471 times higher tendency to have thicker CIMT than subjects with no polymorphism in MCP1 promoter. OPN promoter T-66G was also studied but it did not indicate occurrence of polymorphism in samples.